A neuropsychological instrument measuring age-related cerebral decline in older drivers: development, reliability, and validity of MedDrive - Vaucher, Paul; Cardoso, Isabel; Veldstra, Janet L.; Herzig, Daniela; Herzog, Michael; Mangin, Patrice; Favrat, Bernard (Frontiers in Human Neuroscience, 2014)
When facing age-related cerebral decline, older adults are unequally affected by cognitive impairment without us knowing why. To explore underlying mechanisms and find possible solutions to maintain life-space mobility, there is a need for a standardized behavioral test that relates to behaviors in natural environments. The aim of the project described in this paper was therefore to provide a free, reliable, transparent, computer-based instrument capable of detecting age-related changes on visual processing and cortical functions for the purposes of research into human behavior in computational transportation science. After obtaining content validity, exploring psychometric properties of the developed tasks, we derived (Study1) the scoring method for measuring cerebral decline on 106 older drivers aged ≥70 years attending a driving refresher course organized by the Swiss Automobile Association to test the instrument’s validity against on-road driving performance (106 older drivers). We then validated the derived method on a new sample of 182 drivers (Study2). We then measured the instrument’s reliability having 17 healthy, young volunteers repeat all tests included in the instrument five times (Study3) and explored the instrument’s psychophysical underlying functions on 47 older drivers (Study4). Finally, we tested the instrument’s responsiveness to alcohol and effects on performance on a driving simulator in a randomized, double-blinded, placebo, crossover, dose-response, validation trial including 20 healthy, young volunteers (Study5). The developed instrument revealed good psychometric properties related to processing speed. It was reliable (ICC=0.853) and showed reasonable association to driving performance (R2=0.053), and responded to blood alcohol concentrations of 0.5 g/L (p=0.008). Our results suggest that MedDrive is capable of detecting age-related changes that affect processing speed. These changes nevertheless do not necessarily affect driving behavior.